Pengaruh Sruktur Kepemilikan dan Profitabilitas Terhadap Nilai Perusahaan Dengan Struktur Modal Sebagai Variabel Mediasi Pada Perusahaan Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2024 - Siti Wiliyani; Laila Wardani (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2026)
This study was conducted to examine and analyze the effect of ownership structure and profitability on company value with capital structure as a mediating variable in food and beverage companies listed on the Indonesia Stock Exchange from 2020 to 2024. This type of research is classified as associative research with a quantitative approach. The research data was obtained through the use of survey samples. The population in this study consisted of 86 companies. The sampling technique applied in this study was purposive sampling. Ten companies were sampled, resulting in 50 observations. This study used SPSS 27 and the Sobel test for data analysis. This study shows that institutional ownership structure has a negative and significant effect on capital structure, managerial ownership structure has a negative but insignificant effect on capital structure, and profitability also has a negative and significant effect on capital structure. The study shows that institutional ownership significantly and negatively affects company value, while managerial ownership structure and profitability have a significant positive effect on company value, and capital structure has a positive but insignificant effect on company value. The results of the study indicate that capital structure is unable to act as a mediator in the relationship between institutional ownership structure, managerial ownership structure, and profitability on company value.